Performance of piezoelectric energy harvesters at various angles - Adhes Gamayel; Mohamad Zaenudin; Djoko Setyo Widodo (Universitas Ahmad Dahlan, 2025)
Piezoelectric materials are capable of generating electricity in response to mechanical strain, making them suitable for energy harvesting applications. Piezoelectric energy harvesters (PEHs) are promising alternatives for renewable energy generation, particularly because mechanical strain can be induced in various ways, including utilizing wind flows. This study investigates the performance of a PEH integrated with a laboratory-scale wind-driven micro-windmill. The experiment is carried out by rotating blades of the windmill intermittently; thus, it contacts the PEH, inducing oscillatory motion and generating strain, which finally produces electricity. The configuration angle is varied with 30°, 45°, and 60° to produce variation of power output analyzed in this study. The results demonstrate that a lower configuration angle, specifically 30°, produces the highest voltage near 1.4 V. This is due to the alignment of the applied force with the natural bending direction of the cantilever, resulting in greater induced strain and increased voltage output. Conversely, increasing the configuration angle reduces the effectiveness of force induced to PEH, diminishing strain induction and electrical generation, which only about 1.2 V. The finding of this study can potentially contribute to advance the design and optimization of PEHs for renewable energy applications, particularly in powering microelectronic devices.